2004
DOI: 10.1038/sj.npp.1300543
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intoxication Effects on Simulated Driving: Exploring Alcohol-Dose Effects on Brain Activation Using Functional MRI

Abstract: Driving while intoxicated is a major public health problem. We investigated impaired driving using a simulated driving skill game that presents an 'in-car' view of a road and a readout of speed. We explored brain activation and behavioral alterations from baseline at two blood alcohol concentrations (BACs). Participants received single-blind individualized doses of beverage alcohol designed to produce blood alcohol content (BAC) of 0.04 and 0.08 or placebo. Scanning occurred on a 1.5 Tesla Philips MRI scanner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 35 publications
9
143
1
1
Order By: Relevance
“…S1). Similarly, a data-driven, temporal concatenation ICA approach, combined with dual regression (32)(33)(34), revealed consistent patterns of functional connectivity across centers for 20 spatially independent functional networks ( Fig. 1 and Figs.…”
Section: Resultsmentioning
confidence: 66%
“…S1). Similarly, a data-driven, temporal concatenation ICA approach, combined with dual regression (32)(33)(34), revealed consistent patterns of functional connectivity across centers for 20 spatially independent functional networks ( Fig. 1 and Figs.…”
Section: Resultsmentioning
confidence: 66%
“…Such nonlinear transient components of the BOLD response are well-known for cognitive tasks (Courtney et al, 1997;Postle, Zarahn and D'Esposito, 2000;Konishi, Donaldson and Buckner, 2001;Posse et al, 2001;Huettel, Guzeldere, McCarthy, 2001;Shulman et al, 2001;Zacks et al, 2001;Calhoun et al, 2001Calhoun et al, , 2002ad'Avossa, Shulman and Corbetta, 2003;Krasnow et al, 2003;Calhoun et al, 2004a;Cabeza et al, 2004;Chen and Desmond, 2005;Fox et al, 2005;Meegan and Honsberger, 2005;Scheibe et al, 2006;Vuilleumier et al, 2005) but we are not aware of reports of such transient responses the offset of repeated or steady-state stimulation. In either case, the rectifying nonlinearity of a positive response to both stimulus onsets and offsets goes far beyond any nonlinear properties of the hemodynamic models per se, and implies the operation of a pronounced (rectifying) nonlinearity in the underlying neural response to these stimulation conditions.…”
Section: Discussionmentioning
confidence: 95%
“…However, studies of multiple different response waveforms (Zacks et al, 2001;d'Avossa et al, 2003;Bellgowan et al, 2003;Calhoun et al, 2004a;Fox et al, 2005) have typically identified different cortical regions with differential response dynamics to the same or different stimulus conditions. The issue of multiple components within a given region of cortex is not addressed in these studies.…”
Section: Boldðtþ ¼ Gðnðtþþ ð3þmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered cerebellar activity was associated in a dose-dependent way with impaired driving behavior (Calhoun et al, 2004;Carvalho et al, 2006). Altered cerebellar activity probably disrupts the coordination of eye movements with the actions involved in driving, including steering, just as it disrupts coordination of eye movements and steering on foot, or visually guided stepping, to targets (Crowdy and Marple-Horvat, 2004).…”
Section: Introductionmentioning
confidence: 99%